The Changing Dynamics of Nationalism: A Reading of Select Fiction from Nepal. - Sharma, Meena (SARE: Southeast Asian Review of English, 2023)
The monarchy, Nepali language, and Hinduism have been instrumental in the development of Nepali nationalism, and issues related to ethnicity, language, race, and region have been systematically ignored in the formation of the Nepali state. Likewise, the national literature of Nepal until the 1990s was dominated by writers from the Hindu upper caste who spoke primarily of and for the ruling class, often undermining the diversity of an otherwise heterogeneous nation. However, the political upheavals witnessed by Nepal in the 21st century have led to an upsurge of groups searching for ‘national identities’ on ethnic and regional grounds. This has also brought key changes to the literary landscape of Nepal, and contemporary writers have been increasingly drawn to the emerging new voices and identity movements aimed at questioning the prevalent notion of ‘inclusive nationalism’ with its central axis on the monarchical base and Parbatiya supremacy. Against the backdrop of a renewed debate on nationalism and the structure of the state in Nepal, this paper seeks to examine the changing dynamics of Nepali nationalism as encapsulated in contemporary fiction from Nepal. The paper examines the rising ethnocultural and regional nationalism in Nepal in two contemporary novels, Karnali Blues (2010) and The Wayward Daughter (2018), by two prominent Nepali writers, Buddhisagar Chapain and Shradha Ghale, respectively. Karnali Blues has been hailed as a pioneering work in introducing ‘new regionalism’ in the context of Nepali literature. It narrates the story of mid- and far-western Nepal and aptly captures the lives of groups belonging to the margins. Shradhe Ghale’s The Wayward Daughter focuses on a Janajati family and portrays a rich cross-section of Nepali society influenced by the lived realities of class and caste. The paper explores the diversity of life, region, and population in Nepal as depicted in both novels, thereby validating the necessity to understand Nepali nationalism in terms of region, class, religion, and ethnicity. This is also reflective of the changing narrative of Nepali nationalism. Keywords: Nationalism, Nation, Ethnicity, Regionalism, Religion, Nepal, Fiction